Counterpart. The complete second season [videorecording (DVD)] - Simmons, J. K; Simmons, J. K; Tyldum, Morten; Boniadi, Nazanin, 1980-; Gabriel, Betty (Starz, 2019)
A hapless UN employee discovers that the agency he works for is hiding a gateway to a parallel dimension that's in a cold war with our own, and where his other self is a top spy. The war slowly heats up thanks to spies from both sides.